Design e qualidade: uma análise do processo produtivo de ourivesaria - Lisboa, Maria da Graça Portela (2009)
The present study it consists of a research on the productive processes in the companies of goldsmithery of the central region of the Rio Grande Do Sul, from the practical experience of the production of a jewel collection intitled Gauchidade, divided in three lines: Line Travelling in the South, Line Riding in Pampas and Line Living in the Traditions, developed as final project of graduation of the researcher. During the process of production of jewels, carried through in the Aírton company Jewelers, it was observed that all the phases of the process, that go since the purchase of the raw material until the delivery of the end item to the customer, can be perfected in direction to the total quality. For the analysis of the process the methodologies had been used search bibliographical, 5W2H, mapping of processes and diagram of cause and effect.